2021
DOI: 10.1155/2021/5562517
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Microscopic Investigation of Sarcocystis Species Isolated from Sheep Muscles in Iran

Abstract: Sarcocystis species is a genus of cyst-forming parasites infecting both humans and animals globally. Some of these species cause clinical and subclinical diseases in the host and may lead to economic losses. This study was carried out to identify the distribution patterns of Sarcocystis spp. in slaughtered sheep based on the digestion method and PCR-RFLP in Isfahan, the center of Iran. In total, 150 fresh muscle samples (30 hearts, 60 esophagi, and 60 diaphragms) were investigated by naked eye observation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In the end, only 35 articles were included in this study. Forty sets of data were obtained, including 30 sets on sheep [ 5 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] and 10 on goats ( Figure 2 , Table 1 and Table 2 ) [ 16 , 17 , 36 , 37 , 38 , 41 , 42 , 43 , 44 , 45 ]. Meta analysis data can be downloaded from Supplementary Material .…”
Section: Resultsmentioning
confidence: 99%
“…In the end, only 35 articles were included in this study. Forty sets of data were obtained, including 30 sets on sheep [ 5 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] and 10 on goats ( Figure 2 , Table 1 and Table 2 ) [ 16 , 17 , 36 , 37 , 38 , 41 , 42 , 43 , 44 , 45 ]. Meta analysis data can be downloaded from Supplementary Material .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, DNA analysis with high sensitivity and specificity have been used for the identification of Sarcocystis species. Based on previous studies, 18S rRNA and/or 28S rRNA genes have been implemented as useful genetic markers for identification and differentiation of Sarcocystis in sheep ( 6 , 12 , 14 , 26 ) and goats ( 12 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macroscopic sarcocystosis prevalency was reported to be 4.1% ( 13 ) in domestic sheep in Iraq, 29.3% ( 27 ), 3.3% ( 14 ) in domestic sheep in Iran and 33.6% [1991–1992; ( 11 )] in domestic goats in Iraq and 16.6% [2004; ( 16 )] in goats in Iran. Encouragingly, the present study showed that these infection rates decreased significantly to only 0.01% (20/141, 260) in domestic sheep and 0.02% (9/37, 399) in domestic goats during the winter season 2021–2022.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the supernatant fluid was discarded and sediment was stained with Giemsa and examined microscopically for detecting bradyzoites of Sarcocystis. (Pestechian et al, 2021).…”
Section: Microscopic Examinationmentioning
confidence: 99%